The effect of occupational stressors on health and individual productivity: assessments via sobel test - Zafir Mohd Makhbul,; Sheikh Muhamad Hizam Hj. Sheikh Khairuddin, (Penerbit Universiti Kebangsaan Malaysia, 2014)
Stress is found to significantly affect academics in universities all around the world. The present research examines the issue of stress at the workplace and its effects on the health and individual productivity of the academic administrators at Malaysian research universities (MRUs). The pressure from requirements for research and development at MRUs also contributes to these problems. Based upon the survey of existing literature, stress at the workplace has a negative effect on health. The negative effects on health jeopardize individual productivity. The purpose of the present research is to determine the mediating effects of health on the relationship between occupational stressors and individual productivity. The respondents were selected based upon the proportionate stratified random sampling method. 300 questionnaires were collected from the academic administrators of 5 MRUs. A 100 per cent response rate was obtained. The research instrument used for the stress and health component was adopted from the ASSET (A Shortened Stress Evaluation Tool). Common occupational stressors in the workplace include work relationships; work-life balance; overload; job security; control; resources and communication; and pay and benefits. Meanwhile, health is represented by physical health and psychological well-being. Finally, the productivity of the academic administrators is based upon their common duties and responsibilities, which include teaching, supervision, publication, training, student service, administrative duties and social responsibility productivity. The aforementioned aspects of productivity are considered in the annual performance appraisal reviews of academic administrators performed by the MRUs. The stressors are analyzed dimensionally, while health and individual productivity are measured aggregately. The statistical techniques used in this study include multiple regression analysis and Sobel tests. The results show that certain occupational stressors are significantly, but negatively, related to health, such as work relationships, work-life balance, job security, control and aspects of the job (i.e., physical working conditions, type of tasks and the amount of satisfaction derived from the job). Additionally, certain occupational stressors are found to be significantly, but negatively, related to individual productivity, including work relationships; work-life balance; job security; control; resources and communication; and pay and benefits. Finally, the results indicate that health partially mediates the relationship between work relationships, work-life balance, job security, control and individual productivity.